2019
DOI: 10.1021/acschembio.8b01083
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Ligand Screening Uncovers a RNF4 E3 Ligase Recruiter for Targeted Protein Degradation Applications

Abstract: Targeted protein degradation has arisen as a powerful strategy for drug discovery allowing the targeting of undruggable proteins for proteasomal degradation. This approach most often employs heterobifunctional degraders consisting of a protein-targeting ligand linked to an E3 ligase recruiter to ubiquitinate and mark proteins of interest for proteasomal degradation. One challenge with this approach, however, is that only a few E3 ligase recruiters currently exist for targeted protein degradation applications, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
187
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 239 publications
(200 citation statements)
references
References 49 publications
1
187
0
Order By: Relevance
“…These molecules are generally larger and more flexible than typical drug-like compounds, which can translate into poor membrane permeability and liability to efflux pumps 39,42,43 . While covalent binding to E3 ligases is acceptable 31,44 , PROTACs binding covalently to the protein target probably lose the substoichiometric nature of their mechanism 45 . Finally, what percentage of a target protein should be degraded to trigger a phenotypic response probably depends on the target and the readout, but needs to be systematically investigated.…”
Section: Progress and Lessons Learnedmentioning
confidence: 99%
“…These molecules are generally larger and more flexible than typical drug-like compounds, which can translate into poor membrane permeability and liability to efflux pumps 39,42,43 . While covalent binding to E3 ligases is acceptable 31,44 , PROTACs binding covalently to the protein target probably lose the substoichiometric nature of their mechanism 45 . Finally, what percentage of a target protein should be degraded to trigger a phenotypic response probably depends on the target and the readout, but needs to be systematically investigated.…”
Section: Progress and Lessons Learnedmentioning
confidence: 99%
“…In previous works investigating the direct targets of parthenolide, multiple studies have revealed unique ligandable and functional cysteines within their respective proteins that could be targeted to influence cellular signaling and pathogenicity. Recent studies have shown that activity-based protein profiling (ABPP)-based chemoproteomic platforms can be utilized to uncover unique and functional druggable hotspots and modalities that can be accessed by covalently-acting small-molecules and natural products that may not be obvious using standard drug discovery paradigms (Backus et al, 2016;Bateman et al, 2017;Grossman et al, 2017;Hacker et al, 2017;Spradlin et al, 2018;Ward et al, 2018).…”
Section: Main Textmentioning
confidence: 99%
“…TRH 1-23 (2, Table 2) is a promising RNF4 inhibitor that was recently identified in an activity-based protein profiling (ABPP) screen. An analog of TRH 1-23, named CCW-16 3, was found to be a more a potent RNF4 inhibitor, exhibiting an IC 50 of 1.8 μM [63]. Von Hippel-Lindau (VHL) E3 Ubiquitin Ligase is one of the few E3 ligases, including cereblon, VHL, MDM2, and cIAP, that have been successfully exploited in targeted protein degradation strategies [71,72].…”
Section: Ring-type E3 Ligase Inhibitorsmentioning
confidence: 99%